Hyper screens: the presentation of audiovisual cultural heritage through interactive media platforms and audiovisual documentation in the preparation of news for television news programs / Nik Siti Aisha Amira Nik Masron - Nik Masron, Nik Siti Aisha Amira (2015)
Summary of the articles: “Hyper Screens: The Presentation of Audiovisual Cultural Heritage Through Interactive Media Platforms” and “Audiovisual Documentation in the Preparation of News for Television News Programs”